(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Working has enormous implications for understanding women’s risks of marital violence since it plays such an important role in forming gender expression as well as gender relations. By examining employment as a symbolism, instead of solely economic resource, this research investigates the link between labor market participation and the risk of spousal violence against women. We start with such a latent class analysis, which shows qualitatively diverse patterns of domestic violence. The next step is to look at the direct and indirect effects of employment on women’s risks of experiencing spousal abuse. The influence of a woman’s career on her risks of domestic and family violence is mediated by her spouse’s professional level, according to our results. To a certain extent, these results reflect men’ efforts to exert control over their women partners.